INTERNATIONAL LEGAL ANALYSIS AND REASONS FOR THE IMPLEMENTATION OF TELEMEDICINE IN THE HEALTHCARE SYSTEM OF VARIOUS COUNTRIES - Visolakhon I. Toshmatova; Bobir T. Khalmukhamedov; Nargiza M. Nurillaeva (Central Asian Journal of Medicine, 2022)
Objective of the study: to study the legal framework and analyze the experience of introducing information and communication technologies by some foreign countries into the field of medicine. Material and methods: analysis and generalization of scientific, methodological and foreign literature, a test questionnaire and analysis of results. The testing was carried out on the basis of the questions of the additional professional training program for doctors in the specialty 31.08.54 “general practice”, 31.08.49 “therapy” on the topic “telemedicine in the work of a primary care physician. The survey involved 32 students of the Faculty of General Medicine in the direction of general medicine. Results: About the term telemedicine technologies among 32 interviewed respondents correctly answered - 6 people (18.8%), when asked about the system of identification and authentication of participants in remote interaction when providing medical care using telemedicine technologies - 7 people answered correctly (21.8%), about the procedure for organizing and providing medical care using telemedicine technologies that can be used in the provision of primary health care were answered correctly by 8 (25%) people, about digital photography only 3 people (9.4%) of graduates answered correctly. "What is the main purpose of telemedicine counseling?" - 9 people (28.1%) from 32 respondents answered for this question correctly. The lowest level of knowledge was shown by students in relation to the question of preparing the technical process for conducting a telemedicine consultation, the next question concerned the participants in the telemedicine consultation, and 0% was received in relation to the knowledge of the telemonitoring system. Conclusion: The low level of knowledge of modern information computer technologies by graduates indicates the importance of developing their knowledge in relation to telemedicine consultations, it is necessary to expand the knowledge of graduates about the effectiveness of innovative methods of providing medical services to the population. The latter is relevant during the period of coronavirus infection, in order to avoid direct contact with the sick person and at the same time not leave the patient in a helpless state.